Contemporary Accounting Research: A Retrospective between 1984 and 2021 using Bibliometric Analysis - Baker, H. Kent; Kumar, Satish; Pandey, Nitesh; Kraus, Sascha (Contemporary accounting research, 2023)
ABSTRACT This study critically evaluates research published by Contemporary Accounting Research (CAR) between 1984 and 2021 using bibliometric analysis. We examine the following: (i) CAR's publication quality and the factors associated with its citations and (ii) CAR's scope regarding research diversity, methods, authors geographical dispersion, and collaborative networks. The methodology permits observation of finer collaboration details and research patterns not apparent by simply categorizing the data. We use tools such as performance analysis, coauthorship analysis, bibliographic coupling, and regression analysis. The bibliometric analysis shows improvement in CAR's CiteScore and source‐normalized impact per paper over time, consistent with publishing high‐quality research. Our analysis reveals that authors' geographical affiliations, research subject areas, and research methods are not systematically associated with citations across our various subsamples. A notable exception is that research on audit topics generates more citations than studies examining financial accounting topics. Other factors significantly and positively associated with citations include article age, article length, number of authors, order of author names, and number of references. We also show that CAR has become more diverse regarding author affiliations, subject areas, and research methods than most leading accounting journals. Only Accounting, Organizations and Society emerges as more diverse, thereby serving as a benchmark for CAR in the future. CAR should consider focusing on high‐interest areas to boost citations and tightening its acceptance criteria. RÉSUMÉ Recherche comptable contemporaine : une rétrospective des années 1984 à 2021 basée sur l'analyse bibliométrique Cette étude évalue de façon critique les recherches publiées par Recherche comptable contemporaine (RCC) entre 1984 et 2021 à l'aide d'une analyse bibliométrique. Les auteurs examinent les points suivants : (i) la qualité des publications de RCC et les facteurs associés à ses citations et (ii) la portée de RCC concernant la diversité des recherches, les méthodes, la dispersion géographique des auteurs et les réseaux de collaboration. La méthodologie utilisée permet d'observer des détails de collaboration plus fins et des modèles de recherche qui ne sont pas apparents en classant simplement les données par catégories. Les auteurs utilisent des outils tels que l'analyse de performance, l'analyse des copublications, le couplage bibliographique et l'analyse de régression. L'analyse bibliométrique montre une amélioration du CiteScore de RCC et du Source Normalized Impact per Paper (SNIP) au fil du temps, ce qui correspond à la publication de recherches de haute qualité. La présente analyse révèle que les appartenances géographiques des auteurs ainsi que leurs domaines et méthodes de recherche ne sont pas systématiquement associés aux citations dans les divers sous‐échantillons utilisés. Une exception notable est que la recherche sur les sujets d'audit génère plus de citations que les études examinant les sujets de comptabilité financière. Les autres facteurs associés aux citations de façon significative et positive sont l’âge de l'article, sa longueur, le nombre d'auteurs, l'ordre des noms d'auteurs et le nombre de références. L’étude montre également que RCC est devenue plus diversifiée en ce qui concerne l'appartenance des auteurs, les domaines et les méthodes de recherche que la plupart des grandes revues de comptabilité. Seule la revue Accounting, Organizations and Society apparaît comme plus diversifiée, servant ainsi de point de référence pour RCC à l'avenir. RCC devrait envisager de se concentrer sur les domaines d'intérêt élevé afin d'augmenter les citations et de resserrer ses critères d'acceptation.